1997
DOI: 10.1136/thx.52.5.425
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fitness in patients with cystic fibrosis and mild lung disease

Abstract: Abstracttests, leading to the suggestion that regular Background -Maximal exercise testing is aerobic training may increase life expectancy. 8 used in patients with cystic fibrosis to as-To investigate this important issue, improved sess functional status and prognosis. The methods of quantifying aerobic fitness are relactate threshold is an index of aerobic quired which are not excessively stressful and fitness with significant advantages over are readily acceptable to patients. maximal exercise tests. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Several smaller studies have included lactate measurement in the assessment of peak exercise, and have shown that CF subjects do generate a rise in blood lactate on progressive exercise [16][17][18][19]. The present authors found raised lactate levels at peak exercise in CF patients across the full range of pulmonary disease severity, with those in the middle/ moderate group achieving very similar peak concentrations to controls.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Several smaller studies have included lactate measurement in the assessment of peak exercise, and have shown that CF subjects do generate a rise in blood lactate on progressive exercise [16][17][18][19]. The present authors found raised lactate levels at peak exercise in CF patients across the full range of pulmonary disease severity, with those in the middle/ moderate group achieving very similar peak concentrations to controls.…”
Section: Discussionsupporting
confidence: 62%
“…This is the case in normal subjects at peak exercise, but in the CF subjects this was occurring at lower work rates. The early occurrence of the ''lactate threshold'' during incremental exercise has been reported in patients with mild CF [18], and also in subjects with COPD [24]. The implication of the present lactate data is that CF patients with mild or moderate pulmonary disease are not limited by ventilation, but rather by nonpulmonary factors leading to muscle fatigue.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In particular, airway dead space is independent from V T , thus in cases of reduction in V T the patient has a greater proportion of dead space for each breath. However, several studies in CF patients with mild or moderate pulmonary disease reported increases in lactate levels [125,126,127,128] and early occurrence of the lactate threshold [127] during incremental exercise, indicating an increase in muscle anaerobic metabolism and suggesting that peak exercise is not limited by ventilation, but rather by nonpulmonary factors that lead to leg fatigue. A relatively low V′ E /MVV at peak exercise and high HR reserve supported this interpretation.…”
Section: Exercise Intolerance In Cystic Fibrosismentioning
confidence: 99%
“…Several studies with mild or moderate pulmonary disease reported increases in lactate levels and early occurrence of the lactate threshold during incremental exercise, indicating an increase in muscle metabolism and suggesting that peak exercise is not limited by ventilation, but rather by non pulmonary factors that lead to leg fatigue (Moorcroft et al, 2005, Mc Loughlin et al, 1997, Nikolaizik et al, 1998 In a study included 104 CF who performed progressive cycle ergometry to a symptom limited maximum, the conclusion was that the main factor limiting exercise in mild to moderate disease is peripheral muscle effort (Moorcroft et al, 2005). Reduced muscle performance may be due to poor nutritional status or reduced habitual activity.…”
Section: Factors Limiting Maximal Exercise Performance In Cystic Fibrmentioning
confidence: 99%